PERBANDINGAN MEDIASI DALAM HUKUM ACARA PERDATA INDONESIA DENGAN SINGAPURA: Comparison of Mediation in Indonesia and Singapore Civil Procedure Law - Farhan, Kiagus Muhammad; Kirana, Gandes Candra (AMICUS CURIAE, 2024)
The existence of interactions between individuals makes it possible for disputes to occur, therefore civil procedural law is needed to handle them, and one way to resolve disputes is through mediation. Indonesia and Singapore themselves have mediation regulations in civil procedural law. The problems discussed in this article are the similarities and differences between mediation in the civil procedural law of Indonesia and Singapore and the advantages and disadvantages of mediation in the civil procedural law of Indonesia and Singapore. Normative research type, the nature of the research is descriptive, secondary data using library research, qualitative data analysis, and deductive methods of drawing conclusions. From the results of the discussion, it is known that both Indonesia and Singapore have similarities and differences in implementing mediation and also that both countries have advantages and disadvantages in implementing mediation in their respective countries. The similarities and differences as well as the advantages and disadvantages can be used as a reference for each country in evaluating and innovating the implementation of mediation